Relationships in the family and their impact on the degree of the Internet addiction among school youth - Barbara Niedorys; Monika Mikos; Marcin Stanisław Rząca; Katarzyna Kocka (Journal of Education, Health and Sport, 2018)
Introduction: Family relationships have a huge influence on the personality of a teenager, his future elections, personal and professional development. If the basic emotional needs of family members are not satisfying, there are no family ties between them and the parents’ attitude towards the child are inadequate it may lead to impaired proper development of a young person's identity and development of risky behaviors including the Internet addiction, which is particularly dangerous.